The Effectiveness of Regulations Related to the Relocation of Networked Supermarkets in Tulungagung After the Job Creation Law - Tavia Yuga Ayutia; Surya Anoraga; Fitria Esfandiari; Nur Rohim Yunus (Universitas Muhammadiyah Malang, 2023)
The establishment of the Tulungagung Regional Regulation Number 1 of 2018 concerning the Arrangement and Development of People's Markets, Shopping Centers, and Supermarkets to maintain the economic stability of the surrounding community with regulations to relocate networked shops. After the enactment of Law No. 11 of 2020 concerning Job Creation, namely through the implementing regulations of Government Regulation Number 5 of 2021 which regulates the licensing system through Online Single Submission (OSS). This study will discuss the effectiveness of Article 6 paragraph (2) Tulungagung Regional Regulation No. 1 of 2018 After the enactment of the Job Creation Act to run by existing developments in Tulungagung Regency. The problems that will be studied in this paper are 1) the Effectiveness of Article 6 Paragraph (2) Tulungagung Regional Regulation No. 1 of 2018 after the Employment Creation Law; 2) Obstacles in the implementation of Article 6 Paragraph (2) Tulungagung Regional Regulation No. 1 of 2018 After the Job Creation Act. The research method in this paper uses the type of empirical juridical. This study resulted in the first conclusion, the existence of Article 6 paragraph (2) Tulungagung Regional Regulation Number 1 of 2018 is no longer effective after the enactment of Law Number 11 of 2020 concerning Job Creation through its implementing regulation Government Regulation Number 5 of 2021. Second, regarding the authority to issue permits, the authority to supervise and grant business permits, especially SMEs, is currently in the hands of the central government after the enactment of Government Regulation Number 5 of 2021. There are recommendations, namely: Making changes to existing Regional Regulations and improving the quality of Regency Governments based on supervision in issuing permits by looking at the provisions stipulated in Regional Regulations. Keywords: Effectiveness; Authority; Supervision; Permission. Abstrak Dibentuknya Peraturan Daerah Tulungagung Nomor 1 Tahun 2018 tentang Penataan dan Pembinaan Market Rakyat, Pusat Perbelanjaan dan Toko Swalayan untuk menjaga stabilitas perekonomian masyarakat sekitar dengan adanya aturan untuk melakukan relokasi terhadap toko berjejaring, pasca lahirnya Undang-Undang No. 11 Tahun 2020 tentang Cipta Kerja, yakni melalui peraturan pelaksananya Peraturan Pemerintah Nomor 5 Tahun 2021 yang mengatur mengenai sistem perizinan melalui Online Single Submission (OSS). Sehingga dalam penelitian ini membahas terkait efektivitas pasal 6 ayat (2) Peraturan Daerah Tulungagung No. 1 Tahun 2018 Pasca lahirnya Undang-Undang Cipta Kerja agar berjalan sesuai dengan perkembangan yang ada di Kabupaten Tulungagung. Permasalahan yang akan dikaji dalam tulisan ini adalah 1) Efektivitas Pasal 6 Ayat (2) Peraturan Daerah Tulungagung No. 1 Tahun 2018 Pasca UU Cipta Kerja; 2) Kendala dalam pelaksanaan Pasal 6 Ayat (2) Peraturan Daerah Tulungagung No. 1 Tahun 2018 Pasca UU Cipta Kerja. Adapun metode penelitian dalam tulisan ini adalah menggunakan tipe penelitian hukum empiris. Dalam penelitian ini menghasilkan kesimpulan pertama, keberadaan Pasal 6 ayat (2) Perda Tulungagung No. 1 Tahun 2018 sudah tidak berlaku efektif pasca lahirnya Undang-Undang Nomor 11 Tahun 2020 tentang Cipta Kerja melalui peraturan pelaksananya PP No. 5 Tahun 2021. Kedua, berkaitan dengan kewenangan dalam mengeluarkan izin, kewenangan dalam melakukan pengawasan dan pemberian izin berusaha khususnya UMKM saat ini berada di tangan pemerintah pusat pasca lahirnya PP No. 5 Tahun 2021. Dari penelitian ini peneliti merekomendasikan: Melakukan perubahan terhadap Peraturan Daerah juga meningkatkan kualitas pemerintahan. Keywords: Efektivitas; Kewenangan; Pengawasan; Izin.